2018
DOI: 10.1371/journal.pone.0198228
|View full text |Cite
|
Sign up to set email alerts
|

First natural crossover recombination between two distinct species of the family Closteroviridae leads to the emergence of a new disease

Abstract: Lettuce chlorosis virus-SP (LCV-SP) (family Closteroviridae, genus Crinivirus), is a new strain of LCV which is able to infect green bean plants but not lettuce. In the present study, high-throughput and Sanger sequencing of RNA was used to obtain the LCV-SP full-length sequence. The LCV-SP genome comprises 8825 nt and 8672 nt long RNA1 and RNA2 respectively. RNA1 of LCV-SP contains four ORFs, the proteins encoded by the ORF1a and ORF1b are closely related to LCV RNA1 from California (FJ380118) whereas the 3´ … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…Sequencing of the complete genome revealed that the five conserved nucleotides GAAAT found at the start of the 5′ untranslated regions (UTRs) of RNA1 and RNA2 of the California LCV and of other criniviruses [29,30], were also present at the start of the 5′ UTR of LCV-Can RNA1 and RNA2. However, the 5′ UTRs of LCV-Can showed an additional T at the beginning of the five conserved nucleotides (not attributed to the RACE technique).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sequencing of the complete genome revealed that the five conserved nucleotides GAAAT found at the start of the 5′ untranslated regions (UTRs) of RNA1 and RNA2 of the California LCV and of other criniviruses [29,30], were also present at the start of the 5′ UTR of LCV-Can RNA1 and RNA2. However, the 5′ UTRs of LCV-Can showed an additional T at the beginning of the five conserved nucleotides (not attributed to the RACE technique).…”
Section: Resultsmentioning
confidence: 99%
“…Whether there is a possible effect of host plants on the infecting crinivirus sequence is an intriguing question. This might occur due to recombination events between criniviruses co-infecting a host [30,52].…”
Section: Discussionmentioning
confidence: 99%
“…First, tripartite genome of Potato yellow vein virus contains the gene for the p6 analog in the 3′-terminal region of RNA1 but not in RNA2 as it was found for other criniviruses [119] . Second, the 5′-terminal region of Lettuce chlorosis virus genome contains two short genes coding for hydrophobic proteins, thus it is not clear whether one or both these proteins are required for virus cell-to-cell movement [120] , [121] .…”
Section: Closterovirusesmentioning
confidence: 99%
“…Due to the importance of P10 and P26 gene orthologues group in pathogenicity, its viral cycle in Crinivirus, and the fact that these genes have not been studied in PYVV, it is necessary to know about the variability, evolution and presence of molecular viral variants in potato plants generated by selection pressure, mutations, genetic drift, migration and also inter and intraspecific recombination events. These factors may impact the PYVV infectious capacity within its host and the ability to colonize other plant species, increasing the hosts' range as in tomato plants (Ruiz et al, 2018). Our objective in this study was to analyze the P26 and P10 genes of PYVV isolates from two contrasting geographic regions of Colombia to determine their genetic variability, evolution, and possible relationships with the host.…”
Section: Introductionmentioning
confidence: 99%